Recovery of NanoLuc Luciferase-Tagged Canine Distemper Virus for Facilitating Rapid Screening of Antivirals in vitro - Liu, Fuxiao; Wang, Qianqian; Huang, Yilan; Wang, Ning; Zhang, Youming; Shan, Hu (Frontiers in Veterinary Science, 2020)
Canine distemper virus (CDV), belonging to the genus Morbillivirus in the family Paramyxoviridae, is a highly contagious pathogen, affecting various domestic and wild carnivores. Conventional methods are too cumbersome to be used for high-throughput screening of anti-CDV drugs. In this study, a recombinant CDV was rescued using reverse genetics for facilitating screening of anti-CDV drug in vitro. The recombinant CDV could stably express the NanoLuc® luciferase (NLuc), a novel enzyme that was smaller and “brighter” than others. The intensity of NLuc-catalyzed luminescence reaction indirectly reflected the anti-CDV effect of a certain drug, due to a positive correlation between NLuc expression and virus propagation in vitro. Based on such a characteristic feature, the recombinant CDV was used for anti-CDV assays on four drugs (ribavirin, moroxydine hydrochloride, 1-adamantylamine hydrochloride and tea polyphenol) via analysis of luciferase activity, instead of via conventional methods. The result showed that out of these four drugs, only the ribavirin exhibited a detectable anti-CDV effect. The NLuc-tagged CDV would be a rapid tool for high-throughput screening of anti-CDV drugs.